Applying Quantitative Microstructure Control in Advanced Functional Composites. (9th December 2013) - Heinz, Nicholas A.; Ikeda, Teruyuki; Pei, Yanzhong; Snyder, G. Jeffrey
<x xml:space="preserve">Abstract</x> Microstructure control in functional materials draws from a historical reserve rich in established theory and experimental observation of metallurgy. Methods such as rapid solidification, eutectoid reaction, and nucleation and growth precipitation have all proven to be effective means to produce microstructure relevant for a wide array of applications. Here, the available parameters to control structure morphology, size, and spacing are discussed using thermoelectric composites as an example. Moreover, exploiting different aspects of a material system's phase diagram enables a controlled introduction of nanostructures. While much of this discussion is pertinent to the rapidly developing field of thermal conductivity control in thermoelectric composites, these techniques can be applied to a variety of other material systems where their use may lead to novel electrical, optical, as well as thermal properties of semiconductors and insulators as it has in the past for the mechanical properties of metals.